The end of the Bush doctrine: An analysis of gramsci's ideological hegemony - Ismail, Muhamad Takiyuddin (Universiti Utara Malaysia, 2009)
The end of the Bush doctrine: An analysis of gramsci's ideological hegemony, is an attempt to analyze the effectiveness of the Bush Doctrine from the perspective of ideological hegemony as put forward by Italian Marxist thinker, Antonio Gramsci. The author has identified the sources of Bush’s ideological hegemony and how they served to buttress his domination through his infamous ‘War on Terror’. He has also traced the forces that challenged Bush’s hegemony and how a counter consciousness has evolved. The book ends with a conclusion that the US under the Bush administration tends to rely on domination - coercion, hard power, and deception - to justify the worldview he held.